2007
DOI: 10.1088/0963-0252/16/4/015
|View full text |Cite
|
Sign up to set email alerts
|

Atomic oxygen densities in a downstream microwave O2/Ar plasma source

Abstract: An intense source of atomic oxygen is reported in this paper. Oxygen atoms were produced in an Ar/O 2 , 2.45 GHz, microwave discharge at flow rates ranging from 10 to 150 sccm and pressures from 0.5 to 4 Torr. The absolute flow rate of atomic oxygen peaked at 70 sccm which corresponded to a fractional dissociation close to 0.5. The atomic oxygen flow rate was measured using a titration method with NO 2 gas. It was also shown that the emission ratio from the 3p 3 P state of an oxygen atom at 844.6 nm and from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Since both species are bombarded by the same electron distribution and the concentration of the actinometer is known, the density of the sample can be calculated. To determine the concentration of the ground state oxygen atoms, O (3s 3 P − 3p 3 S) 844 nm and Ar (3p 5 4p (2p 1 ) − 3p 5 4s (1s 2 )) 750.4 nm transitions were chosen and the dissociation fraction can be determined by calculating the ratio 42 45 46 . Here, n l is the number density of ground species l , is the intensity of emission from excited species l for the transition i → j , is the Einstein coefficient, is the spectral response of the system, and is the frequency of the light emission.…”
Section: Resultsmentioning
confidence: 99%
“…Since both species are bombarded by the same electron distribution and the concentration of the actinometer is known, the density of the sample can be calculated. To determine the concentration of the ground state oxygen atoms, O (3s 3 P − 3p 3 S) 844 nm and Ar (3p 5 4p (2p 1 ) − 3p 5 4s (1s 2 )) 750.4 nm transitions were chosen and the dissociation fraction can be determined by calculating the ratio 42 45 46 . Here, n l is the number density of ground species l , is the intensity of emission from excited species l for the transition i → j , is the Einstein coefficient, is the spectral response of the system, and is the frequency of the light emission.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most important initial conditions for the numerical simulations was the concentration of atomic oxygen. To find what concentrations existed in the experiments, an NO 2 titration technique was adopted [47]. The NO 2 was added to the plasma afterglow at the same location of NO injection, approximately 5 ms downstream of the plasma.…”
Section: Reactionmentioning
confidence: 99%
“…Work done by previous authors has shown that application of the actinometry method does not always yield results that reflect the true atomic oxygen number density in the plasma. The validity of actinometry for atomic oxygen has been investigated for various plasma sources: RF capacitive plasma [14,15,16], ECR source [17], DC glow discharge [18], microwave source [19,20], helicon source [21], inductive source [22], and micro-scale atmospheric pressure jet source [23]. Walkrup et al [14] investigated the validity of actinometry for atomic oxygen in RF capacitive plasmas containing both pure O 2 and O 2 /CF 2 mixtures by examining line emission intensity ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Again they found that the method works best for the O * (844)/Ar * (811.5) emission ratio particularly if the dissociation fraction was greater than a few per cent. Ershov et al [20] investigated atomic oxygen actinometry in an Ar/O 2 , 2.45 GHz microwave source and used downstream NO 2 gas titration to measure [O] for comparison. They concluded that actinometry using the O * (844)/Ar * (750) emission ratio was valid for modest Ar/O 2 flow ratios (smaller than 2) when the total pressure in their system exceeded 1 Torr while the O * (777)/Ar * (750) ratio gave misleading results.…”
Section: Introductionmentioning
confidence: 99%